Finding Policies of Disguised Unemployment Arrangement: Through Various Technological Innovation of Agriculture and Income Diversification For Tidal Rice Farmer - Dessy Adriani; Elisa Wildayana (Program Pascasarjana Universitas Sriwijaya, 2019)
The ecological constraint of tidal lands necessitates agricultural innovation in the related area. But technological innovation, however, make the disguised unemployment worsen in tidal land. Income diversification is expected to be a solution to the rising number of disguised unemployment-associated agricultural innovation. Both combined will offer a solution to cope with the issue of disguised unemployment. This study is aimed to analyzing strategies used to cope with disguised unemployment in the tidal agricultural sector through a combination of technological innovation and income diversification. The study was carried out in the tidal lands in Province of South Sumatra, Indonesia in 2017. This study employed a quantitative method with a survey technique. Simple random sampling was conducted to determine each subject population.The analysis was carried out using tabulative, mathematical, and simulation method. Technological innovation in agriculture gave to the rising number of disguised unemployment in tidal agriculture sector. But, with technological innovation and income diversification, disguised unemployment will be decreased and farmers' income will be increased, yet, the productivity will be low. In other words, to cope with the issues of disguised unemployment, technological innovation in the agricultural sector should be accompanied with the income diversification. However, we should be noted that the combination of agricultural technology innovation policy and income diversification affects to decreasing on household productivity The results are, by and large, useful for policy makers in designing in arranging disguised unemployment policies.